Digital curation for cultural and intellectual assets : a Taiwan perspective - Ke, Hao-Ren (2021)
This paper describes the efforts of the National Central Library, Taiwan, in its International Digitalization Project of Rare Books and Domestic Digitization Project of Modern Chinese Books. The former project is a collaboration with the U.S. Library of Congress, University of Washington, University of California, Berkeley, University of Toronto, and the Bibliothèque nationale de France to digitize Chinese rare books. The latter project is a collaboration with the National Taiwan University Library, National Taiwan Normal University Library, National ChengChi University Libraries, National Taiwan Library, National Library of Public Information, together with other public libraries, cultural institutions, and government agencies to digitalize books published in the twentieth century, especially during the period 1911-1949.